PRODUKSI KARET SIR 20CV MENGGUNAKAN FORMULA HIDRAZIN HIDRAT DAN AMMONIUM SULFAT SEBAGAI ADITIF - Vachlepi, Afrizal (Balai Riset dan Standardisasi Industri Palembang, 2018)
The main product of Indonesia natural rubber is SIR 20. The quality improvement can be done by converting the production of natural rubber SIR 20 to SIR 20 constant viscosity (SIR 20CV). The production of natural rubber SIR 20CV need the stabilizing agents among other a mixture of hydrazine hydrate and ammonium sulfate. The research purpose was to find out and to study the formulation and dosage of the mixture hydrazine hydrate and ammonium sulfate on the production of constant viscosity rubber. This research used factorial completely randomized design with the treatment factor consist of percentage of mixture hydrazine hydrate-ammonium sulfate (treatment A), additive dosage (treatment B) and control (HNS and blank/without additive). The treatment A consists of 50%:50% (A1), 70%:30% (A2), and 30%:70% (A3). The treatment B consists of 0.05% (B1), 0.10% (B2), 0.15% (B3) and 0.20% (B4). Parameters were latex coagulation condition, dry rubber content, and technical quality (initial plasticity/Po, plasticity retention index/PRI, Mooney viscosity/MV, stability viscosity index/SVI, volatile content and ash content). The analysis of technical quality was compared with requirements of SNI 06-1903-2000 about SIR. The results showed that the use of mixed additives of hydrazine hydrate and ammonium sulfate had a significant effect on the parameter pH of latex coagulation, dry rubber content, plasticity, Mooney viscosity, and viscosity stability index of the rubber SIR 20CV. The best treatment was obtained by the treatment of A3B1, which is 30% hydrazine hydrate and 70% ammonium sulfate with a dosage of 0.05%, because could produce natural rubber SIR 20CV with grade CV-70 in accordance with SNI 06-1903-2000.